Downconversion mechanoluminescence from lanthanide codoped heterojunctions - Tianlong Liang; Yuantian Zheng; Qi’an Zhang; Ziyi Fang; Mingzhi Wu; Yang Liu; Qidong Ma; Jiazhen Zhou; Maryam Zulfiqar; Biyun Ren; Yanze Wang; Jingnan Zhang; et al. (Materials Futures)
During the downconversion process, a high-energy photon undergoes conversion into several low-energy photons, leading to enhanced luminous efficiency in both photoluminescent and electroluminescent devices. This phenomenon has been applied in various fields, including solar cells, plasma display panels, and green lighting technologies such as mercury-free fluorescent lamps. However, the concept of downconversion (quantum cutting) has not been fully explored in the context of mechanoluminescent materials. In this study, we successfully synthesized a heterojunction of CaF _2 /CaZnOS exhibiting efficient downconversion mechanoluminescence (ML) properties. By controlling the CaF _2 to CaZnOS ratio and incorporating Tb ^3+ doping, we obtained a highly effective heterojunction structure that significantly enhanced ML. Moreover, we extended this material to several commonly utilized downconversion ion-doping combinations, achieving enhanced ML for Tb ^3+ , Pr ^3+ , and Yb ^3+ single ions. For the first time, we demonstrate the downconversion (quantum cutting) ML of Tb ^3+ –Yb ^3+ and Pr ^3+ –Yb ^3+ pairs within heterojunction microstructures. This study presents the design and synthesis of a novel heterojunction material capable of realizing downconversion ML, which holds promise for future applications in diverse fields.